Digital Audio Workstation (DAW) sebagai Media Alternatif Penyusunan Komposisi Karawitan Bali - Komang Wahyu Dinata; I Pt. Lukita Wiweka Nugraha Putra (Journal of Music Science, Technology, and Industry, 2025)
Purpose:Balinese karawitan is a cultural heritage characterized by its intricate musical structures and profound philosophical meanings. However, its conventional composition process, transmitted orally and through direct interaction among musicians, faces limitations in documentation, experimentation, and efficiency. This study aims to explore the potential of Digital Audio Workstations (DAWs) as an alternative medium for composing Balinese karawitan, while also examining the opportunities and challenges that arise from integrating digital technology with gamelan traditions.Method:This research employs a qualitative approach using literature study. Data were collected from academic journals, conference proceedings, and books relevant to the use of DAWs in traditional music, particularly Balinese gamelan. The analysis focused on the role of DAWs in timbral experimentation, rhythmic visualization, digital documentation, remote collaboration, and hybrid innovations, and compared these aspects with conventional practices of karawitan composition.Result and Discussion:The findings indicate that DAWs offer significant potential as tools for creative experimentation, long-term digital archiving, and cross-cultural collaboration. They also enable hybrid innovations that merge traditional gamelan instruments with modern electronic elements, thereby expanding the artistic spectrum of Balinese karawitan. Nonetheless, challenges persist, including the limited authenticity of digital sound reproduction, cultural conservatism, unequal technological literacy among traditional musicians, and intellectual property issues regarding gamelan sampling. Therefore, DAWs should be regarded as complementary rather than substitutive to conventional methods, ensuring that Balinese karawitan maintains its cultural authenticity while adapting to the dynamics of modern music technology.